Budidaya Ikan dan Sayur untuk Ketahanan Pangan Rumah Tangga Warga Jemaat GBI Swiss Ministry Denpasar - Maharani, Ida Ayu; Putu Widiadnyana; Ni Putu Dilia Dewi (Direktorat Penelitian, Pengabdian Masyarakat, dan HKI Institut Teknologi dan Bisnis STIKOM Bali, 2025)
The high dependence of urban communities on fluctuating food supplies from the market poses a serious challenge to achieving household food security. The congregation of GBI Swiss Ministry Denpasar is one such community affected by this issue, facing limited land availability and a lack of knowledge regarding urban farming technologies. This community service program aimed to enhance food self-sufficiency among church members through training on Budikdamber (catfish cultivation in buckets), a simple and practical aquaponics-based system. The program was carried out in several stages, including needs assessment, technical socialization, cultivation training, and distribution of Budikdamber kits equipped with automatic feeders and digital guide posters. The results showed high enthusiasm from participants and increased practical understanding of seed and seedling management, as well as integrated food production systems. This training not only provided a practical solution to limited space but also laid the foundation for household-based community food security. The program is expected to serve as a replicable model of community empowerment in other areas facing similar challenges.